Implementasi Blended learning Berbasis Digital untuk Meningkatkan Hasil Belajar Siswa SMKN 6 Bulukumba - Altim, Muhammad Zainal; Syarifuddin, Andi; Basalamah, Abdullah; Delvina, Tanridio Silviaty; Saad, Andi Muhammad; Salmiah, Salmiah (Universitas Pahlawan Tuanku Tambusai, 2025)
UPT SMK Negeri 6 Bulukumba has great potential in producing graduates who are ready to work thanks to the expertise programs offered. The digital-based blended learning program has been implemented as part of the government's efforts to develop quality vocational education, but it needs to be further improved. Based on this, the purpose of implementing PKM activities is to implement blended learning using digital platforms and applications in the implementation of learning. The methods applied are lecture and material delivery methods, discussion and participation, practice, and mentoring. The results obtained from this PKM activity are that the overall implementation of the activity went quite well and in accordance with the set time target. The effectiveness of the implementation of blended learning for students before and after implementation shows a significant increase that has a positive impact on improving students' critical thinking skills and learning outcomes. The response of students and teachers in terms of satisfaction level is quite good. The average percentage of improvement in student learning outcomes reached around 25.33%, which reflects a significant increase in student learning outcomes. This shows that the implementation of digital-based blended learning has a stronger and very positive impact.